An overview in urban geology and urban geomorphology - Bathrellos, G. D. (Bulletin of the Geological Society of Greece, 2007)
Worldwide is observed an expansion in urban areas. In Greece a proportional phenomenon is mentioned. More than 52% of the Greek population now lives in the two metropolitan municipalities of Athens and Salonica. For this reason grows up the scientific interest to urban geology and urban geomorphology. Urban Geology is the application of geologic knowledge to the planning and management of metropolitan areas. Its domain spans both regional geology and applied geology. Urban Geomorphology is the study of man as a physical process of change whereby he metamorphoses a more natural terrain to an anthropogene cityscape. In such a context Urban Geomorphology is the surface component of Urban Geology, which is one of the important subfields of environmental geology. The urban geomorphology is related with the management of natural hazards and the spatial planning. Engineering geology and urban planning need to interface with geomorphology in hazardous areas.